Migration and Residual Trapping of Immiscible Fluids during Cyclic Injection: Pore-Scale Observation and Quantitative Analysis - Haejin Ahn; Seon-Ok Kim; Minhee Lee; Sookyun Wang (Geofluids)
Geological CO2 sequestration (GCS) is one of the most promising technologies for mitigating greenhouse gas emission into the atmosphere. In GCS operations, residual trapping is the most favorable form of a trapping mechanism because of its storage security and capacity. In this study, the effects of cyclic injection of CO2-water on the immiscible displacement and residual trapping in pore networks were examined. For the purpose, a series of injection experiments with five sets of drainage-imbibition cycles were performed using 2D transparent micromodels and a pair of proxy fluids, n-hexane, and deionized water. The multiphase flow and immiscible displacement phenomena during drainage and imbibition processes in pore networks were visually observed, and the temporal and spatial changes in distribution and saturation of the two immiscible fluids were quantitatively estimated at the pore scale using image analysis techniques. The results showed that the mobile region of invading fluids decreased asymptotically as the randomly diverged flow paths gradually converged into less ramified ones over multiple cycles. Such decrease was accompanied by a gradual increase of the immobile region, which consists of tiny blobs and clusters of immiscible fluids. The immobile region expanded as streams previously formed by the insertion of one fluid dispersed into numerous isolated, small-scale blobs as the other fluid was newly injected. These processes repeated until the immobile region approached the main flow channels. The observations and analyses in this study implied that the application of cyclic injection in GCS operations may be used to store large-scale CO2 volume in small-scale dispersed forms, which may significantly improve the effectiveness and security of geological CO2 sequestration.